The impact of intermittent normobaric hypoxia-hypoxic training on the blood and biochemical parameters of an athlete - Sheshurina T. A.; Slepova D. A.; Kalinin A. V.; Dorofeykov V. V.; Lomazova E. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the impact of intermittent hypoxia-hypoxic training on the biochemical and hematological characteristics of an athlete.